Service Quality Improvement Strategies Through Strengthening Organizational Culture, Transformational Leadership, Self-Efficacy, and Work Engagement - Zubaidah, Siti; Hardhienata, Soewarto; Sunaryo, Widodo (International Journal Labs, 2024)
This study aims to analyze the improvement of service quality through strengthening organizational culture, transformational leadership, self-efficacy, and work engagement. The types of data in this study are quantitative data and qualitative data. Research data collection was carried out using a questionnaire to respondents. In this study, the data analysis stage begins with descriptive variable analysis, prerequisite test analysis, and continued with path analysis. The results showed that 1) there is a significant direct positive effect of organizational culture (X1) on service quality (Y), 2) there is a significant direct positive effect of transformational leadership (X2) on service quality (Y), 3) there is a significant direct positive effect of self-efficacy (X3) on service quality (Y), 4) there is a significant positive direct effect of organizational culture (X1) on work engagement (X4), 5) there is a significant positive direct effect of transformational leadership (X2) on work engagement (X4), 6) there is a significant positive direct effect of self-efficacy (X3) on work engagement (X4), 7) there is a significant positive direct effect of work engagement (X4) on service quality (Y), 8) there is a significant positive indirect effect of organizational culture (X1) on service quality (Y) through work engagement (X4), 9) there is a significant indirect positive effect of transformational leadership (X2) on service quality (Y) through work engagement (X4), 10) there is a significant indirect positive effect of self-efficacy (X3) on service quality (Y) through work engagement (X4).